GUIDANCE AND COUNSELING MANAGEMENT STRENGTHENING STUDENTS’ CHARACTER EDUCATION - Nur Istianah; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Education should not only transfer academic knowledge but also develop students' moral awareness, social responsibility, and character resilience. However, schools continue to face disciplinary problems, weak responsibility, and negative student behavior, while guidance and counseling services are often managed reactively and have not been fully integrated into a systematic managerial framework. This study aims to analyze guidance and counseling management in strengthening students' character education and to formulate an adaptive conceptual model based on the functions of planning, organizing, actuating, and controlling. This research employed a qualitative library research design. Data were collected through documentation of relevant books, journal articles, theses, dissertations, and policy documents related to guidance and counseling management and character education. The data were analyzed using content analysis through data reduction, thematic categorization, interpretation, and conceptual synthesis. The findings show that guidance and counseling management contributes to character strengthening through needs-based program planning, collaborative organization involving school stakeholders, direct implementation of individual, group, and classical services, and measurable evaluation of character outcomes. The literature also indicates that actuating is the most dominant aspect, while controlling and evaluation remain underdeveloped. The study proposes an adaptive, cyclical model consisting of value-based orientation, needs-based planning, system-based organizing, character-oriented actuating, and sustainable controlling. This model positions guidance and counseling as a strategic school system for developing discipline, responsibility, honesty, empathy, and noble character.